Effect of Carbide Distribution on the Grain Refinement in the Steel for Large‐Size Bearing Ring. Issue 6 (17th July 2015) - Dong, Zhengqiang; Jiang, Bo; Mei, Zhen; Zhang, Chaolei; Zhou, Leyu; Liu, Yazheng
Abstract: The effect of carbide distribution on the grain refinement in the steel for large‐size bearing ring is investigated. It is observed that Ni‐containing steel has an obvious grain refinement below 1050 °C, whereas its grain growth trend is steeper than that of Ni‐free steel above 1050 °C. No evident segregation of Ni is observed, whereas the pinning effect of carbides distributed along grain boundaries is advantageous for the grain refinement. It is found that Ni addition could affect the type of carbides and contribute to decreasing the size of carbides via accelerating the diffusion of carbon. A stronger pinning effect with smaller carbides distributed along grain boundaries could be obtained, which is beneficial to grain refinement with Ni addition in small amounts. Abstract : Ni addition could contribute to decreasing the size and affecting the type of carbides. Carbides with smaller size are beneficial to the pinning effect and result in a better effect of grain refinement.